Assessing workflow of emergency physicians in the use of clinical decision support. (November 2019) - Salwei, Megan E.; Carayon, Pascale; Hoonakker, Peter; Hundt, Ann Schoofs; Novak, Clair; Wang, Yudi; Wiegmann, Douglas; Patterson, Brian
The emergency department (ED) is a complex environment where diagnoses must often be made quickly, based on incomplete information. Pulmonary embolism (PE) is an especially challenging diagnosis that is frequently delayed or missed due to its non-specific symptoms, and can be life-threatening when not treated. Clinical decision supports (CDS) have the potential to improve these difficult decisions; however, previous efforts to implement CDS in the ED have faced challenges due to poor usability and lack of workflow integration. The objective of this study is to identify potential barriers to workflow integration from the technology's implementation and inform the CDS design; this is achieved by analyzing ED physicians' workflow during a usability evaluation of two different CDS, a web-based risk scoring CDS and a CDS designed using an human-centered design (HCD) process and human factors (HF) design principles. The number of cases matching the guideline-based workflow and the percent of correct diagnostic decisions increased from the use of the HF-based CDS, but varied depending on the patient scenario. We identified three workflow variations, which had both positive and negative implications for the CDS design and implementation. The workflow analysis can be used to inform the CDS design and improve the technology's usability and integration in physician workflow prior to implementation.